Strengthening pill press control to combat fentanyl: Legislative and law enforcement imperatives - Nicholas Lassi (Elsevier, 2023)
Background: Fentanyl has garnered significant focus from governments, academics, and the media due to the unparalleled increase in overdose fatalities it has triggered in North America. However, the pill presses, dies, and molds used to tablet counterfeit fentanyl-laced pills in Mexico and the United States (U.S.) have gone largely unstudied despite their substantial influence on fentanyl production. The Biden-Harris administration's recent initiative to intensify the prosecution of illicit fentanyl supply chains and the U.S. Treasury Department's decision to impose sanctions on numerous Chinese entities for illicit pill press production and distribution highlights the need to increase controls on pill-press proliferation. Objective: Review the existing legislative frameworks and enforcement in the U.S., China, and Mexico that pertain to pill press control and provide recommendations for improvement. Methods: A literature review was conducted to gather information on counterfeit fentanyl-laced pill production, pill press control, and related legislative frameworks and enforcement in the U.S., China, and Mexico. Federal and state laws, policies, and enforcement mechanisms were reviewed to identify gaps, limitations, and potential for improvement. A comparative study was then performed to determine the strengths and weaknesses of these states' prevailing legislative structures and enforcement mechanisms. Results: In the U.S., pill press laws at the federal level are limited, and state laws are generally weak or nonexistent. The U.S. Controlled Substances Act should be amended to include harsher penalties for the unregistered possession of pill presses with or without the intent to tablet illicit substances. China, the primary source of illicitly distributed pill presses, does not have laws regulating pill presses and should enact strong pill press legislation and engage in rigorous enforcement. Conclusions: As pill presses are integral to the final and crucial step in counterfeit fentanyl-laced pill production, pill press control should receive more legislative and law enforcement attention in the U.S., China, and Mexico.